An account on the Orthoptera from Siargao Island (Southeast Asia: Philippines: Mindanao) - Tan, Ming Kai; Baroga-Barbecho, Jessica B.; Yap, Sheryl A. (Zootaxa, 2019)
Siargao Island is located on the southeastern part of the Philippines. We have very little knowledge on the Orthoptera from this island which is covered with forest over limestone, open vegetation, and mangrove, despite being designated as one of the terrestrial Key Biodiversity Areas (KBAs) in the Philippines. We conducted surveys in 2018 to search for orthopterans. In total, thirty-seven species from 34 genera were found. Seventeen species are recorded in Siargao Island for the first time, representing 45.9% of all collected species, thus, validating that orthopterans in the island are indeed overlooked. Out of the 37 species, 21 of these are endemic to the Philippines and 9 are endemic to Siargao Island, hence suggesting that species on the island can be biologically significant.. We also observed that a huge proportion of the species in Siargao Island are fully winged and capable of flight, but most species are small sized. We also provide taxonomic notes and illustrations, including descriptions of the male Segestidea punctipennis Bolívar, 1903 and female Eumecopoda reducta Hebard, 1922 for the first time. We inferred that species from Siargao Island are closely associated with Sundaland and for within Philippines, Mindanao and Luzon.